2020
DOI: 10.1142/s1088424619501062
|View full text |Cite
|
Sign up to set email alerts
|

Heteroleptic palladium(II) complexes of dipyrrin-1,9-dione supported by intramolecular hydrogen bonding

Abstract: The dipyrrin-1,9-dione framework, which is characteristic of the propentdyopent pigments deriving from heme metabolism, coordinates metal ions as monoanionic bidentate donors. The resulting analogs of dipyrrinato complexes undergo reversible ligand-based reductions, thus showcasing the ability of the dipyrrindione scaffold to act as an electron reservoir. Herein we report the synthesis and characterization of three heteroleptic palladium complexes of the redox-active dipyrrindione ligand. Primary amines were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(34 citation statements)
references
References 49 publications
5
29
0
Order By: Relevance
“…67,68 In this context, we sought to investigate the ability of the dipyrrindione framework to host unpaired spins in a bridged dinuclear system. In our previous investigations of the palladium(II) dipyrrindione complexes featuring primary amine ligands (e.g., [Pd(en)(pdp)] + , Chart 2d), 52 we found that the intramolecular hydrogen bonds are important for complex stability. This observation prompted us to explore the synthesis of a similar diaqua complex.…”
Section: Chart 2 Tetraethyl Propentdyopent-methanol Adduct (A) and Reported Complexes (B-d)mentioning
confidence: 85%
See 3 more Smart Citations
“…67,68 In this context, we sought to investigate the ability of the dipyrrindione framework to host unpaired spins in a bridged dinuclear system. In our previous investigations of the palladium(II) dipyrrindione complexes featuring primary amine ligands (e.g., [Pd(en)(pdp)] + , Chart 2d), 52 we found that the intramolecular hydrogen bonds are important for complex stability. This observation prompted us to explore the synthesis of a similar diaqua complex.…”
Section: Chart 2 Tetraethyl Propentdyopent-methanol Adduct (A) and Reported Complexes (B-d)mentioning
confidence: 85%
“…Monitoring the reaction progress via optical absorption spectroscopy, we observed the gradual decrease of the single absorption band of Hpdp•MeOH at 280 nm accompanied by the growth of two main bands at 382 and 545 nm, consistent with our previous reports on dipyrrindione complexes. 50,52 In the course of our synthetic manipulations, we observed that exposing a dichloromethane solution of this red complex to an aqueous wash resulted in an immediate color change of the organic phase from red to blue. The absorption spectrum of the blue solution in CH2Cl2 presents a shift in the main bands to 372 and 585 nm (Figure 1, Table S1), clearly indicating the formation of a different species.…”
Section: Synthesis and Chemical Characterizationmentioning
confidence: 94%
See 2 more Smart Citations
“…The Suzuki-Miyaura cross-coupling is an important tool in organic chemistry with active research in the development of new palladium catalysts. 135 Surprisingly, while homo-and heteroleptic Pd(II) dpm complexes have been extensively investigated, 33,[136][137][138][139][140][141][142][143][144][145] only one report described the potential of these compounds for C-C bond formation. 140 Mono-and bi-nuclear heteroleptic complexes 64 and 65 (Fig.…”
Section: Pd(ii) Based Catalystsmentioning
confidence: 99%